1998
DOI: 10.1289/ehp.981069
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of chlorpyrifos on residential surfaces and toys accessible to children.

Abstract: Quantitative examination of major pathways and routes of exposure to pesticides is essential for determining human risk. The current study was conducted in two apartments and examines the accumulation of the pesticide chlorpyrifos in childrens' toys after the time suggested for reentry after application. It has been established for the first time that a semivolatile pesticide will accumulate on and in toys and other sorbant surfaces in a home via a two-phase physical process that continues for at least 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(146 citation statements)
references
References 25 publications
7
137
1
1
Order By: Relevance
“…2,69,75 According to the literature, children in general ingest about 50 mg/day house dust during the summer and 100 mg/day during the winter, when they spend more time indoors. 57,58 In the case of pica behavior (eating of non-nutritive substances), uptake can reach up to 2--30 g/day.…”
Section: Resultsmentioning
confidence: 99%
“…2,69,75 According to the literature, children in general ingest about 50 mg/day house dust during the summer and 100 mg/day during the winter, when they spend more time indoors. 57,58 In the case of pica behavior (eating of non-nutritive substances), uptake can reach up to 2--30 g/day.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated surface concentrations coupled with their frequent hand-to-mouth activities would likely result in exposure through non-dietary ingestion (Gurunathan et al, 1998;Cohen-Hubal et al, 2000;Freeman et al, 2005;Hore et al, 2005). In all, 33% of parents reported that their children played in the room where the insecticide had been applied earlier that day.…”
Section: Exposure Scenarios Resulting From Insecticide Applicationmentioning
confidence: 99%
“…Young children are considered to be especially susceptible to the harmful effects of pollutants both because their bodies are immature and developing rapidly, and because their behavior, such as testing new objects with their mouths, may increase their exposures (Zahm and Devesa, 1995;Heil et al, 1996;Gurunathan et al, 1998;Mukerjee, 1998;Landrigan et al, 1999;Cohen Hubal et al, 2000a, b;Freeman et al, 2001a, b;Tulve et al, 2002). Children's exposures can come from several media, including air, dust, soil, and food.…”
Section: Introductionmentioning
confidence: 99%